ASIMILASI LONTARA PANGADERENG DAN SYARI'AT ISLAM: Pola Perilaku Masyarakat Bugis-Wajo - Nawawi, Nurnanigsih (AL-TAHRIR, 2015)
Abstract: This study is aimed at showing the concepts of cultural values of Bugis society in Wajo, comprising of the values such as honesty, expertness, truth, mercy, and business summarized in the system of "pangedereng". These values could be traced through the historical records of sureâ€™ Galigo / lontara, written in the sixteenth century. This investigation use qualitative research with data collection obtained from library and field, as well as interviews. Data sources include 'Sureâ€™ Galigo Ritumpa'na Walenrengnge and manuscripts containing the Lontara advice from kings and Bugis wise men. Research findings indicated that the values were assimilated with the Islamic shari'a, in which its most values were strongly tied to the principle of siriâ€™ (respectability). This principle serves as the basis of ethics and attitudes and is expected to be motivation, especially, for the young generations who live in the globalization era and are heavily loaded with the influence of scientific and technological development on one hand and are lack of moral, cultural, and religious values on the other hand.Â Ø§Ù„Ù…Ù„Ø®Øµ: Ø§Ø³ØªÙ‡Ø¯Ù Ø§Ù„Ø¨ØØ« Ø¥Ù„Ù‰ ØªÙ‚Ø¯ÙŠÙ… ØªØµÙˆØ± Ø¹Ù† Ø§Ù„Ù‚ÙŠÙ… Ø§Ù„Ø«Ù‚Ø§ÙÙŠØ© Ù„Ù„Ù…Ø¬ØªÙ…Ø¹ Ø§Ù„Ø¨ÙˆØºÙŠØ³ÙŠ Ø¨ÙˆØ§Ø¬Ùˆ Ø§Ù„ØªÙŠ ØªØ´ØªÙ…Ù„ Ø¹Ù„Ù‰ Ø¹Ø¯Ù‘Ø© Ù‚ÙŠÙ… ÙˆÙ‡ÙŠ Ø§Ù„Ø«Ø¨Ø§ØªØŒ Ùˆ Ø§Ù„Ø°ÙƒØ§Ø¡ØŒ Ùˆ Ø§Ù„ØµØ¯Ù‚ØŒ Ùˆ Ø§Ù„Ù…ÙˆØ¯Ø©ØŒ Ùˆ Ø§Ù„Ø¬Ø¯Ù‘ÙŠØ© ÙÙŠ Ø§Ù„Ø³Ø¹ÙŠ. ÙˆØªØªÙˆØÙ‘Ø¯ Ø§Ù„Ù‚ÙŠÙ… ÙÙŠ ØµÙˆØ±Ø© "pangadereng" Ø§Ù„Ù…ÙˆØ¬ÙˆØ¯Ø© ÙÙŠ Ø§Ù„ÙˆØ«Ø§Ø¦Ù‚ Ø§Ù„ØªØ§Ø±ÙŠØ®ÙŠØ© "sureq galigo/lontara" ÙˆÙƒØ§Ù† Ø¥Ø¨ØªØ¯Ø§Ø¡ ÙƒØªØ§Ø¨ØªÙ‡Ø§ ÙÙŠ Ø§Ù„Ù‚Ø±Ù† XVI . Ø§Ø³ØªØ®Ø¯Ù… Ù‡Ø°Ø§ Ø§Ù„Ø¨ØØ« Ø§Ù„Ù…Ø¯Ø®Ù„ Ø§Ù„ÙƒÙŠÙÙŠ Ù…Ø¹ Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ø§Ù„Ù…ØµØ¯Ø±Ø© Ù…Ù† Ø§Ù„Ù…ÙƒØªØ¨Ø© ÙˆØ§Ù„Ù…ÙŠØ¯Ø§Ù† ÙˆØ§Ù„Ù…Ù‚Ø§Ø¨Ù„Ø©. ÙˆÙ…Ù† Ø§Ù„Ø¨ÙŠØ§Ù†Ø§Øª Ù‡Ùˆ "sureq galigo ritumpakna walenrenge/lontara" Ø§Ù„Ø°ÙŠ ÙŠØ´Ù…Ù„ Ø§Ù„ÙˆØµØ§ÙŠØ§ Ù…Ù† Ø§Ù„Ù…Ù„ÙˆÙƒ Ùˆ Ø§Ù„ØÙƒÙ…Ø§Ø¡ Ø§Ù„Ø¨ÙˆØºÙŠØ³ÙŠÙŠÙ†. Ø¯Ù„Ù‘Øª Ù†ØªØ§Ø¦Ø¬ Ø§Ù„Ø¨ØØ« Ø£Ù† Ø§Ù„Ù‚ÙŠÙ… ØªØªÙˆØÙ‘Ø¯ Ù…Ø¹ Ø§Ù„Ø´Ø±ÙŠØ¹Ø© Ø§Ù„Ø¥Ø³Ù„Ø§Ù…ÙŠØ© ÙˆÙÙŠÙ‡Ø§ ØªØ¹Ø§Ù„ÙŠÙ… "siri" . ÙˆÙŠØ±Ø¬Ù‰ Ø£Ù† ØªÙƒÙˆÙ† Ù‡Ø°Ù‡ Ø§Ù„Ù‚ÙŠÙ… Ø¯Ø§ÙØ¹Ø§ â€“ Ø®Ø§ØµØ© Ù„Ù„Ø´Ø¨Ø§Ù† - ØØªÙ‰ ÙŠØ³Ù„ÙƒÙˆØ§ Ù…Ø³Ù„Ùƒ Ø¢Ø¨Ø§Ø¦Ù‡Ù…ØŒ ÙˆÙ‡Ù… Ø¹Ø§Ø´ÙˆØ§ ÙÙŠ Ø¹ØµØ± Ø§Ù„Ø¹ÙˆÙ„Ù…Ø© Ø¨Ù…Ø§ ÙÙŠÙ‡ Ù…Ù† Ø¢Ø«Ø§Ø± ØªÙ‚Ø¯Ù… Ø§Ù„Ø¹Ù„ÙˆÙ… ÙˆØ§Ù„ØªÙƒÙ†ÙˆÙ„ÙˆØ¬ÙŠØ§ Ù…Ù† Ø¬Ù‡Ø©ØŒ ÙˆÙ…Ù† Ø¬Ù‡Ø© Ø£Ø®Ø±Ù‰ ÙƒØ§Ù†ÙˆØ§ Ø¨Ø¹ÙŠØ¯ÙŠÙ† Ø¹Ù† Ù‚ÙŠÙ… Ø§Ù„Ø£Ø®Ù„Ø§Ù‚.Abstrak: Penelitian ini bertujuan mengemukakan konsep-konsep nilai budaya bagi masyarakat Bugis Wajo yang meliputi nilai-nilai kejujuran, kecendikiaan, kebenaran, kasih sayang, dan usaha, yang terangkum dalam sistem "pangedereng", dapat ditelusuri melalui catatan sejarah sureg Galigo / lontara. Penulisan dimulai pada abad ke XVI. Penelitian ini menggunakan metode kualitatif dengan pengumpulan data perpustakaan, lapangan, dan wawancara. Data antara lain berupa Sureg Galigo Ritumpa'na Walenrengnge serta naskah-naskah lontara yang memuat petuah raja-raja dan orang bijak Bugis. Penemuan yang bersifat nilai tersebut terasimilasi dengan syariat Islam yang senantiasa dinafasi "SIRI" dari bertingkah laku dan diharapkan dapat menjadi motivasi terutama bagi generasi muda yang hidup di arena globalisasi yang sarat dengan pengaruh IPTEK di satu sisi dengan kekosongan moral, budaya, dan agama di sisi lain.Keywords: Pangadereng, asimilasi, Islam, Bugis Wajo